Biodegradation of tert-butyl alcohol (TBA), and treatment of TBA contaminated wastewater by aerobic granules - Zhuang, Weiqin (2008)
The focus of this study is the biodegradation of tert-butyl alcohol (TBA) and the complete biological removal of TB A from contaminated water using aerobic granulation system. Aerobic granulation is a novel biological wastewater treatment technology which has several benefits as compared to the conventional activated sludge systems. Aerobic granules are dense and compact microbial aggregates with good settling capabilities, good bioactivity, larger biomass retention, and good resistance to chemical toxicity. TBA was chosen as a model compound in this study because of its high recalcitrance and inhibitory characteristics. The aims of this study were to evaluate the utility of the sequencing batch reactor (SBR) to acclimate microorganisms towards biological removal of TB A, to cultivate TB A-degrading aerobic granules in SBR using TBA as sole carbon and energy source, to isolate and characterize TB A-degrading pure microbial cultures, and to elucidate a TBA degradation mechanism of aerobic granules achieved via microbial interaction.